Effect of Electrochemically Activated Water on the Quality Indicators of Dough and Wheat Flour Products - Alexander G. Pogorelov; Artem I. Panait; Alexander L. Kuznetsov; Elena N. Molchanova; Oleg A. Suvorov; Larisa G. Ipatova (Техника и технология пищевых производств, 2022)
Electrochemically activated water has a high physicochemical and biological activity. It interacts with food ingredients and affects the baking process in a different way than untreated water. The research objective was to study the effect of the anodic and cathodic fractions of electrochemically activated water on the quality indicators of wheat flour, dough, and bread. The study featured electrochemically activated water fractions, wheat flour, yeast, dough, and wheat bread. It employed standard physicochemical and organoleptic methods of analysis to study the redox potential and pH of electrochemically activated water during relaxation. The indicators returned to the initial level, but they changed significantly after 72 h. The experiment included the quantity and quality of gluten, extensibility and hydration, water-retaining capacity of flour, yeast fermentation, titratable acidity, dough fermentation rate, and the quality of finished products. The anolyte did not change the quality of gluten but decreased its amount by 2.0–3.7%, probably due to a weaker protein hydration. As for the effect of catholyte on the quality of gluten, the bonds between proteins became stronger in weak as the measurement of gluten deformation index decreased by 11.3%; they relaxed in stronger as the measurement of gluten deformation index increased by 20%. Catholyte increased the water-retaining capacity of weak flour by 11.7% and that of resistant gluten – by 5.3%. It also activated yeast cells. The samples of bread cooked on catholyte had a greater specific volume by 3.7–5.4% and porosity – by 2.3–4.6%, compared to the samples cooked on anolyte. The research also included a comparative analysis of the shape of the hearth bread samples. It confirmed that the catholyte strengthened the dough when the flour was weak and relaxed it when resistant gluten was used. The research revealed some patterns regarding the effect of electrochemically activated water fractions on the amount and properties of gluten, water-retaining capacity of flour, yeast activity, and bread quality indicators. The results can be used to correct the properties of dough from low-quality flour, as well as for reagent-free control of the properties and behavior of food and biological raw materials.